2022
DOI: 10.1055/a-1694-5552
|View full text |Cite|
|
Sign up to set email alerts
|

Echinococcosis: a Challenge for Liver Sonography

Abstract: The sonographic findings in alveolar echinococcosis (AE) and cystic echinococcosis (CE) are complex and can pose significant differential diagnostic problems. They may present like complicated cysts or malignant tumors in the liver. We will discuss the diagnostic difficulties and pitfalls of these two diseases based on case histories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
0
11
0
9
Order By: Relevance
“…AE and CE are two completely different diseases [11]. There are signi cant differences between CE and AE in the morphology, epidemiology, histopathology, clinical course, clinical management and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…AE and CE are two completely different diseases [11]. There are signi cant differences between CE and AE in the morphology, epidemiology, histopathology, clinical course, clinical management and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Even though according to the WHO Informal Working Group on Echinococcosis (WHO-IGWE), ultrasound is the preferred tool for screening and diagnosing hepatic CE ( 4 ) , pulmonary manifestation is not always detectable by US because of known physical limitations of lung US. Nevertheless, it was shown that B-mode US was able to detect and diagnose pulmonary CE with high specificity by using the wall sign ( 2 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Darüber hinaus zeigt es eine zentripetale Kontrastmittelanflutung mit komplettem oder inkomplettem Irisblendenphänomen sowie eine hyperechogene Darstellung in der Spätphase; dies ist bei hämangiomartigen AE-Läsionen nicht nachweisbar ( Abb. 8 ) 3 .…”
Section: Fuchsbandwurmerkrankungunclassified
“…Hierbei stellen komplizierte Zysten und nicht typische Raumforderungen die Untersucher vor die Frage: Handelt es sich um eine atypische benigne Läsion oder eine bisher nicht bekannte primär maligne oder metastasensuspekte Läsion [2]? Die sonografischen Befunde bei der Fuchsbandwurmerkrankung (alveoläre Echinokokkose, AE) und der Hundebandwurmerkrankung (zystische Echinokokkose, CE) sind komplex und können erhebliche differenzialdiagnostische Probleme bereiten [3].…”
Section: Introductionunclassified
See 1 more Smart Citation